LIFE SKILL EDUCATION TERHADAP KETERAMPILAN PRA VOKASIONAL MEMBUAT Â ICE CREAM PUTAR ETAWA TUNANETRA - RAMADHAN PRATAMA PUTRA, ALFIN (Jurnal Pendidikan Khusus, 2015)
ABSTRACT Blindness had impact to children’s ability in developing self potential in socializing therefore they required self developing by giving learning life skill before socializing (pre vocational). It was done in order that the blind could live autonomously after socializing and having proper job and could support their life. The job done was not only a massage or a music player but also other jobs. In this case, the children were given learning program of life skill education of making etawa cycle ice cream to enhance their pre vocational ability. The research purpose was to enhance pre vocational of the blind students in SMPLB Bhakti Wanita Lumajang. This research used research arrangement of one group pre test – post test design, with 6 blind students they were 1 total and 5 low vision characteristics. The data analysis of this research used statistic non parametric with sign test kind. From the result of data analysis it could be concluded that the counting number of ZH = 2,05, the number was then compared with critic value 5% ZH = +1,96. The result indicated ZH > 1,96 which meant that Ho was refused and Ha was accepted so it could be stated that “there was influence of using life skill education toward pre vocational skill of making etawa cycle ice cream to the blind students in SMPLB Bhakti Wanita Lumajang.   Keywords: Life skill education, pre vocational